A simplified numerical method to determine the shear stress relaxation time parameters by the example of polymers - Voronin, M.S. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2017)
A numerical method to determine the parameters of the shear stress relaxation time is discussed. This function is one of the constitutive equations of a Maxwellian viscoelastic model. The method is based on a simplification of the system of equations describing the deformation of a thin rod when this system is considered at the yield stress point. The method allows one to find the relaxation time parameters responsible for the yield stress description in a wide range of temperatures and strain rates. The numerical results obtained by the method are compared with experimental data for polymethylmethacrylate, polytetrafluoroethylene, and epoxy resin.